Human insecurity in East Asia - Umegaki, Michio; Thiesmeyer, Lynn; Watabe, Atsushi (United Nations University Press, 2009)
Threats to human security do not necessarily take cataclysmic forms such as war or natural disaster, nor does human insecurity exist solely within a suspended living environment like refugee camps. This publication explores less obvious threats to human security and how people and communities face them.--Publisher's description.